The Role of Teachers in Preventing Juvenile Delinquency in SMA Negeri 4 Surabaya - Luluk utami; Rahmat Arofah Hari Cahyadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Abstract: This research aimed to describe and analyze critically about the role of religious teachers in overcoming juvenile delinquency students of SMA Negeri 4 Surabaya. The research was a qualitative research. The data collection conducted by conducting observation, interview and documentation. The data analysis in accordance with descriptive research conducted with induction mindset. The results showed: (1) The role of religious teachers against juvenile students is very good, because juvenile students needed the role of adults in shaping noble and good personality to avoid delinquency in big cities (2) some kind of delinquency conducted by SMA Negeri 4 Surabaya students included disobedient to parents and teachers, skipping school, and how to wear the uniform dressing less polite (3) The role of religious teachers in preventing juvenile delinquency was very important, religious teachers in preventing juvenile delinquency work together with teachers who as counseling guidance (BK) and the principal of SMA Negeri 4 Surabaya and community leaders, by doing preventive action, repressive and curative action. Keywords: Role, Religious Teacher, Juvenile, Delinquency